Evaluation of the efficiency of energy complexes with the production of hydrogen, oxygen, heat and electricity - Yu. E. Nikolaev; M. A. Aidarov (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE of the research. The global trend of decarbonization of the national economies of the leading countries of the world implies an increase in energy production due to renewable energy sources and hydrogen. The most environmentally friendly way to produce hydrogen is the electrolysis of water using wind and solar energy. Combined production of thermal, electric energy, hydrogen and oxygen carried out by energy complexes ensures reduction of harmful emissions and increase of their economic efficiency.METHODS. In solving this problem, the method of computational experiment was used, taking into account the geographical and climatic data of the location of the energy complex, as well as the nature of consumption of thermal, electric energy and hydrogen. The calculation was implemented in Visual Basic.RESULTS. The article describes the relevance of the topic, examines the influence of the installed capacity of photovoltaic converters, geographical, climatic and cost characteristics on the efficiency of the energy complex.CONCLUSION. The structure is determined and a schematic diagram of a multi-purpose energy complex is proposed. A methodology for calculating quantitative and economic indicators of the installation has been developed. In the course of the study, it was noted that there is an optimal value of the installed capacity of a photovoltaic installation, further increase of which is inexpedient from an economic point of view. It was also determined that the combination of hydrogen gas stations based on solar installations with traditional sources of energy supply can reduce the cost of hydrogen produced, which in the future may be a solution to the problem of creating a hydrogen infrastructure.